Origin and outcome of multiple pregnancies in Bern, Switzerland, 1995–2006 and the current proposal of the Swiss parliament to revise the Swiss law of reproductive medicine: Switzerland quo vadis? (Swiss Medical Weekly, 2013)
INTRODUCTION: Infertility treatments are a major source of the increase in multiple pregnancies (MPs). AIMS: The aims of the present study were (1.) to investigate the origin and maternal/neonatal outcomes of MP and (2.) to review the different measures that can be adopted to reduce these serious complications. METHODS: The study included all women with multiple births between 1 January 1995 and 31 December 2006 at the University Hospital of Bern, Switzerland. The outcomes associated with the various origins of MP (natural conception, ovarian stimulation [OS] ‒ in-vitro fertilisation [IVF-ICSI]) were analysed using a multinomial logistic regression model. An analysis of the Swiss law on reproductive medicine and its current proposed revision, as well as a literature review using Pubmed, was carried out. RESULTS: A total of 592 MP were registered, 91% (n = 537) resulted in live births. There was significantly more neonatal/maternal morbidity in MP after OS compared with natural conception and even with the IVF-ICSI group. With a policy of elective single embryo transfer (eSET), twin rates after IVF-ICSI can be reduced to